Penegakan Hukum Terhadap Penyalahgunaan Narkotika Di Indonesia - Rayani Saragih; Maria Ferba Editya Simanjuntak (Mahesa Research Center, 2021)
This study aims to analyze law enforcement against narcotics abuse in Indonesia and and inhibiting and supporting factors as well as efforts to overcome barriers to law enforcement in law enforcement against narcotics crime in Indonesia. The pre-emptive done as early as possible in form of informal seminar and local counseling to the society about the dangerous effect of illegal drug use. The preventive effort was implementing through series of Routine Police Operation and Special Police Operation. While the repressive efforts were law enforcement action through criminal investigation and indictment which rooted within legality aspect. Each effort still encounters several problems, such as lack of personnel, insufficient equipment, breach of information and lack of operational funds. The type of research used is qualitative research, with the type of research being descriptive. Data collection techniques are carried out by means of observation, and study of documents.